Energi Terbarukan dan Ekonomi Syariah: Sinergitas Mewujudkan Sustainable Development - Azwar Iskandar; Khaerul Aqbar; Sulkifli Herman (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The urgency of the availability of renewable energy, green economy and implementation of Sharia Economy actually has a spirit that is in line with the efforts of the global community in supporting sustainable development. The synergy between Sharia Economy practices in Indonesia and renewable energy programs in order to realize it becomes an inevitability. This research aims to describe the concept of synergy of Sharia Economy practices and renewable energy programs in Indonesia in order to realize sustainable development. This research is qualitative descriptive research through library study methods and content analysis. The results showed that the synergy scheme between renewable energy programs and Islamic economic/financial practices can be done in the form of: (i) sharia financial sector can be an instrument of EBT investment financing; (ii) the utilization of EBT may be a supporter and spearhead of halal industry, such as halal food and beverages, Muslim fashion, halal tourism, pharmaceuticals and halal cosmetics and halal media and recreation; and (iii) in the context of socially religious EBT financing, EBT can be done with the concept of ta'āwun and sedekaj jariah through crowd funding and waqf. In order to optimize the synergy between renewable energy programs and sharia economy, some steps and Quick Wins programs that can be done are: (1) campaigns against the excellence of renewable energy to achieve national energy self-sufficiency; (2) create easy access and attractive financing schemes to support renewable energy; (3) conduct research and publication on renewable energy and potential collaboration with other industries in the halal value chain that can be perceived in Indonesia, especially halal tourism.Keywords: renewable, energy, Islamic, economic, sustainable AbstrakUrgensi ketersediaan energi terbarukan, green economy dan implementasi Ekonomi Syariah sesungguhnya memiliki ruh yang sejalan dengan upaya masyarakat global dalam mendukung pembangunan berkelanjutan. Sinergitas antara praktik Ekonomi Syariah di Indonesia dan program energi terbarukan dalam rangka mewujudkannya menjadi sebuah keniscayaan. Penelitian ini bertujuan untuk mendeskripsikan konsep sinergitas praktik Ekonomi Syariah dan program energi terbarukan di Indonesia dalam rangka mewujudkan pembangunan yang berkelanjutan (sustainable development). Penelitian ini merupakan penelitian deskriptif kualitatif melalui metode studi pustaka dan content analysis. Hasil penelitian menunjukkan bahwa skema sinergitas di antara program energi terbarukan dan praktik ekonomi/keuangan Syariah dapat dilakukan dalam bentuk: (i) sektor keuangan Syariah dapat menjadi instrumen pembiayaan investasi EBT; (ii) pemanfaatan EBT dapat menjadi pendukung dan ujung tombak industri halal, seperti makanan dan minuman halal, fesyen muslim, pariwisata halal, farmasi dan kosmetik halal dan media dan rekreasi halal; dan (iii) dalam konteks pembiayaan EBT yang bersifat sosial keagamaan, EBT dapat dilakukan dengan konsep ta’āwun dan sedekah jariah melalui urun dana (crowd funding) dan wakaf. Dalam rangka mengoptimalkan sinergitas antara program energi terbarukan dan ekonomi Syariah, beberapa langkah dan program Quick Wins yang dapat dilakukan adalah: (1) kampanye terhadap keunggulan energi terbarukan untuk mencapai swasembada energi nasional; (2) menciptakan kemudahan akses dan skema pembiayaan yang menarik untuk mendukung energi terbarukan; (3) mengadakan riset dan publikasi mengenai energi terbarukan dan potensi kolaborasi dengan industri lain dalam rantai nilai halal yang dapat diaplikasikan di Indonesia, terutama pariwisata halal. Kata kunci: terbarukan, energi, Islam, ekonomi, sustainable